Integrated modelling and simulation method of hybrid systems based on X language - Kunyu Xie; Lin Zhang; Xiaohan Wang; Kunyu Wang; Yingjie Li (IET Collaborative Intelligent Manufacturing)
Abstract Model‐based systems engineering is now leading the way in supporting the design of complex products or systems. The integration of modelling and simulation of continuous‐discrete hybrid systems is the key of model‐based systems engineering. But the existing languages, formalisms and tools cannot support the unified modelling and simulation of hybrid systems and therefore reduces the efficiency of complex system development. To address this issue, this paper develops a design method of complex hybrid systems, which integrates modelling and simulation of the continuous‐discrete hybrid behaviour. Specifically, the authors provided a modelling method of hybrid systems based on the X language, a simulation method based on XDEVS, and a compilation algorithm to transform the hybrid model constructed with X language into XDEVS simulation files. In this way, the X language hybrid model can be automatically translated into XDEVS simulation files by a compiler. The simulation files can then be simulated by the XDEVS simulation engine. The obtained simulation results will be used to verify whether the design scheme meets the design requirements of the hybrid system. Finally, the correctness and feasibility of the proposed method are verified using a car‐driving model.